Contention resolution in WDM optical packet switching networks using wavelength converters and cascaded auxiliary switch - Mellah, H.; Abbou, F. M. (2006)
In this paper, a contention resolution scheme for OPS Networks is proposed. The optical switch is augmented using auxiliary output ports connected to an auxiliary switch through wavelength converters. The node architecture is illustrated and the results of the model show that packet blocking probability is improved using the proposed scheme.